Ionic conduction in composite MG30 polymer electrolytes / Noor Ayunie Nasir - Nasir, Noor Ayunie (2010)
Polymer is an important constituent of composite polymer electrolyles(CPE).The potential of 30% poly(methyl methacrylate) grafted natural rubber (MG30) as a polymer host, zinc chloride (ZnCb) as a salt, propylene carbonate (PC) as a plasticizer and titanium dioxide (Ti02) as a inorganic filler. Impedance spectroscopy technique was carried out in order to to determine electrical conductivity value.The highest conductivity value of solid polymer electrolytes which is MG30 added with salt is 2.389 x 10"5 S/cm with 60 wt.% of ZnCl2 at room temperature.CPE was prepared by adding the highest conductivity of SPE with the plasticizer and filler. The ionic conductivity was investigated by using impedance spectroscopy. The highest conductivity of 2.38 x'10"4 S/cm was obtained from 30 wt.% of Ti02 nanofiller at room temperature.